Healthcare Provider Perspectives on HIV Cure Research in Ghana - Lamptey, H.; Newcomb, B.; Bonney, E.Y.; et al. (Hindawi, 2023)
Introduction. Antiretroviral therapy (ART) has reduced mortality and improved life expectancy among HIV patients but does not provide a cure. Patients must remain on lifelong medications and deal with drug resistance and side efects. Tis underscores the need for HIV cure research. However, participation in HIV cure research has risks without guaranteed benefts. We determined what HIV healthcare providers know about HIV cure research trials, the risks involved, and what kind of cure interventions they are likely to recommend for their patients. Methods. We conducted in-depth qualitative interviews with 39 HIV care providers consisting of 12 physicians, 8 counsellors, 14 nurses, 2 pharmacists, 2 laboratory scientists, and 1 community advocate from three hospitals. Interviews were transcribed verbatim and coded, and thematic analysis was performed independently by two investigators. Results. Participants were happy about the success of current treatments and hopeful that an HIV cure will be found in the near future, just as ART was discovered through research. Tey described cure as total eradication of the virus from the body and inability to test positive for HIV or transmit the virus. In terms of risk tolerance, respondents would recommend to their patients’ studies with mild to moderate risks like what patients on antiretroviral therapy experience. Participants were reluctant to recommend treatment interruption to patients as part of a cure study and wished trials could be performed without stopping treatment. Healthcare providers categorically rejected death or permanent disability as an acceptable risk. Te possibility of fnding a cure that will beneft the individual or future generations was strong motivations for providers to recommend cure trials to their patients, as was transparency and adequate information on proposed trials. Overall, the participants were not actively seeking knowledge on cure research and lacked information on the various cure modalities under investigation. Conclusion. While hopeful for an HIV cure, healthcare providers in Ghana expect a cure to be defnitive and pose minimal risk to their patients.
Research Article
Keywords: Antiretroviral therapy; HIV patients; Ghana; Cure; Healthcare Provider